The Effect of Financial Literacy and Income Which Is Moderate by Lifestyle on Financial Behavior (Study of Karawang Regency Civil Servants) - Gilang Raharja; Dasman, Sunita (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to examine the influence of financial literacy and income moderated by lifestyle on financial behavior in Karawang district civil servants. The sampling method in this research is probability sampling using the Slovin formula. The sample in this study was 100 Karawang district civil servants. This research tests correlation and regression with the help of the SMARTPLS 4.0 program, used to test validity and reliability, goodness of fit and hypotheses. Based on the results of this research, it can be concluded that: 1). The financial literacy variable partially has a significant effect on the financial behavior of civil servants in Karawang district. 2). The income variable partially has a significant effect on the financial behavior of civil servants in Karawang district. 3). The financial literacy variable which is partially moderated by lifestyle has no effect and is not significant on the financial behavior of civil servants in Karawang district. 4). The income variable which is moderated by lifestyle partially has a significant effect on the financial behavior of civil servants in Karawang district.